Biofouling Role in Mariculture Environment Restoration: An Example in the Mar Grande of Taranto (Mediterranean Sea) - Arduini, Daniele; Borghese, Jacopo; Gravina, Maria Flavia; Trani, Roberta; Longo, Caterina; Pierri, Cataldo; Giangrande, Adriana (Frontiers in Marine Science, 2022)
The biodiversity of macrobenthic invertebrates of two artificial hard substrates close to a mariculture plant was assessed in order to understand the effect on the fouling community of an innovative Integrated Multi-Trophic Aquaculture (IMTA) system. The examined hard substrates were (i) vertical bare collectors that are placed around the cages as new colonizable substrates, which were investigated from the early colonization and (ii) artificial hard substrates already present under the cages analyzed over time to observe changes due to the action on the water column by filter feeder organisms colonizing the above vertical collectors. Overall, 186 taxa were collected (both the substrates), of which 99 as sessile habitat-former or structuring macroinvertebrates and 87 as associated fauna, mostly vagile forms. On the vertical collectors 121 taxa were collected, among which 44 sessile structuring species and 77 vagile-associated taxa; on the artificial hard substrates under the cages, 124 taxa were identified, 95 belong to the first category and 29 as associated taxa. The two analyzed substrates shared 43% of sessile species (40) and 22% of associated species (19). At the end of the first year of experimentation, the study revealed Sabella spallanzanii and mussels as the most abundant taxa. Lastly, the communities under the cages showed an increase in biodiversity after the placement of collectors. The changes were attributed to the decrease in particulate matter originating as wastes from the breeding cage, which was intercepted by the filter feeder community developed on the vertical collectors.